PRELIMINARY STUDY OF STUDENT EXPERIENCES IN USING BIOLOGY TEXTBOOK BASED ON COLLABORATIVE LEARNING MODEL TO PRACTICE SCIENTIFIC LITERACY SKILLS (Proceedings of the International Conference on Education, 2021)
Science literacy skills are needed in 21st century learning. As a developing country, schools in Indonesia should create learning that is able to practice these skills. The learning strategy that requires students to explore and use scientific knowledge to solve problems is collaborative learning. The collaborative learning model is suitable for learning that is closely related to environmental problems, one of which is biology. Therefore, this study aims to determine the level of understanding of students related to biology (ecosystem) material, to find out students' experiences related to-based textbooks collaborative learning, and to find out the conditions of biology learning that have been applied in schools. This type of research is descriptive quantitative. The research subjects were 30 students of SMAN 1 Ngunut. Data collection techniques were carried out by observation, tests, and questionnaires. The sample of respondents was taken by purposive sampling on the advice of the Biology teacher. The results of this study are as follows: 1) In terms of the level of understanding related to biological material (ecosystem), it is classified as lacking. 2) Students' experiences in learning biology so far have never found the collaborative learning textbook. 3) Learning activities to practice scientific literacy skills are rarely carried out. After adding up the average percentage of each indicator, it is known that the students' understanding is still in the lacking category with a percentage of 44.8%, so that better knowledge and readiness are still needed so as to be able to achieve the 21st century learning goals. One of the steps to solve this problem is to use learning resources that train a lot of scientific literacy skills. The majority of teachers through the survey also agree that the limitations of learning media to train scientific literacy skills can be circumvented by developing textbook-based collaborative learning. Therefore, it can be concluded that textbooks based on collaborative learning model need to be developed.
Keywords: textbook; collaborative learning; ecosystem; scientific literacy